Pengaruh model pembelajaran team games tournament (TGT) berbantuan mathopoly terhadap minat belajar matematika siswa kelas V SDN 82 kota bengkulu - Eka Putri, Tessy Amelia; Agusdianita, Neza; Amaliyah, Yuli (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
This study aims to determine the effect of the Team Games Tournament (TGT) learning model assisted by Mathopoly on the mathematics learning interest of fifth-grade students at SDN 82 Bengkulu City. This research is a quantitative study using a quasi experimental method, with the design applied being the matching only posttest control group design. The population of the study consists of all fifth-grade students at SDN 82 Bengkulu City, with the sample being class VD as the experimental group and class VC as the control group, selected using the cluster random sampling technique. Data were collected through a post-test questionnaire based on predetermined indicators. The results of the hypothesis test show that the t-count value is greater than the t-table value (2.715 > 0.3081), and the significance value (2-tailed) is 0.010 < 0.05. These results indicate a significant difference in students’ interest in learning mathematics between the experimental and control groups, which is attributed to the different instructional treatments-where the experimental group used the TGT model assisted by Mathopoly media, while the control group did not. Based on the analysis, it can be concluded that the alternative hypothesis (Ha) is accepted, meaning that the TGT learning model assisted by Mathopoly has an effect on increasing the mathematics learning interest of fifth-grade students at SDN 82 Bengkulu City.